Team Games Tournament: A Cooperative Model for Training Prosocial Behavior in Early Childhood - Utami, Winda Sherly; Putri, Ayu Aprilia Pangestu (UNIB Press, 2025)
Prosocial behavior is a very important aspect to be taught to children from an early age. This is because prosocial behavior can affect children's ability to interact and manage emotions when dealing with others. This study aims to test the effect of the team games tournament model in training prosocial behavior in children aged 5-6 years. This type of research is quantitative research with a pre-experimental approach, using a one group pretest-posttest design without a control group. The sample used was 15 children aged 5-6 years. Data collection was carried out through observation and documentation. The data analysis technique used a hypothesis test (paired sample t-test). The results of the study showed a significant difference between the conditions before and after the application of the team games tournament model. This model has been proven effective in training prosocial behavior in children aged 5-6 years. It was concluded that the prosocial behavior of children at that age increased after the application of the team games tournament model in the learning process